Ultrasonic devices for trapping and transportation of medicine pills - Ngern, Yen Lee. (2009)
In this final year project, ultrasonic techniques are explored in the view to collect, separate and transport small particles. Current existing ultrasonic actuators are only able to trap micro-scale particles in the air. The heaviest particle that can be collected by the current technology is the grass seed (0.00038g/particle) [18]. Thus in this project, a Dual L-Shaped metal strips ultrasonic actuator is built that has the ability to collect small-scale particles in the air. This actuator is competent to collect a particle that is at least 65 times heavier than what the current actuators can do. The trapping capability of this actuator is investigated. In order to maintain the weight of the various shapes of pill, clay had been used to make the pill. With this, the experiments produced a more accurate result as it eliminated the discrepancy in weight. More specific experiments had been conducted to identify the different factors affecting the trapping capability. These include shape of the pill and orientation of the pill. Through the experiments, it was realized that the trapping capability of the pill is proportional to the surface area of the pill, in contact with the tip of the actuator. Besides that, there is also an experiment to investigate the height of water level rise due to the varying length of the actuator, submerged in 2 different mediums – water and oil. In this experiment, the aluminum plate is dipped into the medium and the height of water level rise is recorded. This is done repeated, varying the length of the actuator, submerged in the medium. From this experiment, the optimized length of the actuator, submerged in the medium, that induced the highest water level rise is 3cm. Furthermore, it is also noticed that there is a memorizing effect as the water level rise did not drop back to the original level upon switching off of the power supply. Through these experiments, many factors, affecting the trapping capability of the actuator, were identified. Besides that, some problems, regarding the setup and procedures of the experiment, were also recognized. As such, various recommendations, pertaining to the problems, were listed in the Chapter 15 of the report.